Leveraging CAR macrophages targeting c-Met for precision immunotherapy in pancreatic cancer: insights from single-cell multi-omics - Lingyu Hu; Xiaoguang Wang; Zhengwei Song; Fei Chen; Bin Wu (Molecular Medicine)
Abstract Background Pancreatic cancer is known for its poor prognosis and resistance to conventional therapies, largely due to the presence of cancer stem cells (CSCs) and aggressive angiogenesis. Effectively targeting these CSCs and associated angiogenic pathways is crucial for effective treatment. This study leverages single-cell multi-omics to explore a novel therapeutic approach involving Chimeric Antigen Receptor (CAR) macrophages engineered to target the c-Met protein on pancreatic CSCs. Methods We employed single-cell RNA sequencing to analyze pancreatic cancer tissue, identifying c-Met as a key marker of CSCs. CAR macrophages were engineered using a lentiviral system to express a c-Met-specific receptor. The phagocytic efficiency of these CAR macrophages against pancreatic CSCs was assessed in vitro, along with their ability to inhibit angiogenesis. The in vivo efficacy of CAR macrophages was evaluated in a mouse model of pancreatic cancer. Results CAR macrophages demonstrated high specificity for c-Met + CSCs, significantly enhancing phagocytosis and reducing the secretion of angiogenic factors such as VEGFA, FGF2, and ANGPT. In vivo, these macrophages significantly suppressed tumor growth and angiogenesis, prolonging survival in pancreatic cancer-bearing mice. Conclusion CAR macrophages targeting c-Met represent a promising therapeutic strategy for pancreatic cancer, offering targeted elimination of CSCs and disruption of tumor angiogenesis. This study highlights the potential of single-cell multi-omics in guiding the development of precision immunotherapies.